DEVELOPING WRITING SKILLS THROUGH ONLINE SELF-REGULATED LEARNING - Cahyaning Imani; Ive Emaliana (Sanata Dharma University, Yogyakarta, 2021)
As a side effect of the emergency transition to remote online learning, all Indonesian schools and universities have stopped teaching in classroom settings in mid-March 2020 and began using internet platforms to deliver online learning activities. However, there are issues concerning students' perseverance and achievement as fully online learning is implemented. Considering many learners may not be able to concentrate on studying under traumatic circumstances, such as a pandemic, it is necessary to consider learning strategies that produce learning opportunities for all students to achieve specific goals in distance learning. Writing skills are considered the most challenging of all language skills among English as foreign language (EFL) students. When students use an online self-regulated learning (OSEL) strategy in learning writing, they can control their performance and benefit from online learning by adjusting their behaviors. Thus, the aim of the study is to find the causal relationship between OSEL strategy and writing skills.